DESAIN WORKSPACE MULTIFUNGSI SEBAGAI PENUNJANG KUALITAS KERJA - Syaifuddin Zuhri; Astrini Hadina Hasya; Ratna Andriani Nastiti (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2022)
The workbenches that are often found today were originally designed with universal needs in mind. In general, workbench designs that are often encountered in design studios do not consider the work area and storage area. One of the problems that arise from this design is the limited access to storage of design work and design work using manuals and computers. This study discusses the design of a work desk that carries a multifunctional concept. The design of the workspace that carries this multifunctional concept is important to do in order to provide solutions to the problems that have been encountered. This study uses the design thinking method in producing design solutions. Observations were made on the users of the workbench first and then informal interviews related to the level of work comfort were carried out. To support the production process, material selection and product finishing are also carried out in order to obtain products that have good quality. Next, analysis of user needs is carried out to generate design ideas. The result of this study is the design of a multifunctional workbench by considering the complexity of work requirements in order to support the quality of the user's work. This workbench design can be used as a reference for product development, especially on the design of a workbench that can be used in a design studio.